2021
DOI: 10.1021/acsomega.1c04825
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology-Based Analysis on the Action Mechanism of Oleanolic Acid to Alleviate Osteoporosis

Abstract: Oleanolic acid (OA) is a triterpenoid commonly found in plants and has shown extensive pharmaceutical activities. This study aimed to investigate the underlying mechanism of antiosteoporosis (OP) action of OA by utilizing the network pharmacology approach and molecular docking methods. First, the targets of OA were identified using the GeneCards, Stitch, and Swisstarget databases, and the targets related to OP were mined using the NCBI, Genecards, and DisGeNet databases. The overlapped targets of OA and OP wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Furthermore, GO analysis revealed that bosutinib mainly influences extracellular structure organization, extracellular matrix organization, sterol biosynthetic process, secondary alcohol biosynthetic process, and cholesterol biosynthetic process (Figure B). Pathways enrichment analysis using GO and KEGG revealed several pathways related with bone metabolism or bone-related disease, including extracellular matrix organization, steroid biosynthesis, TNF signaling pathway, as well as starch and sucrose metabolism. PCA showed that the difference between groups is obvious (Figure S1D). Venn diagram analysis revealed that 382 and 297 genes were specifically expressed in hUCMSCs induced with and without bosutinib, respectively, with 10830 genes co-expressed between the two groups (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, GO analysis revealed that bosutinib mainly influences extracellular structure organization, extracellular matrix organization, sterol biosynthetic process, secondary alcohol biosynthetic process, and cholesterol biosynthetic process (Figure B). Pathways enrichment analysis using GO and KEGG revealed several pathways related with bone metabolism or bone-related disease, including extracellular matrix organization, steroid biosynthesis, TNF signaling pathway, as well as starch and sucrose metabolism. PCA showed that the difference between groups is obvious (Figure S1D). Venn diagram analysis revealed that 382 and 297 genes were specifically expressed in hUCMSCs induced with and without bosutinib, respectively, with 10830 genes co-expressed between the two groups (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…OA proved useful in bone tissue regeneration by modulating Notch signaling and growth factor bone morphogenetic protein 2 (BMP2); the phytocompound induced mesenchymal stromal cell (MSC) osteogenic differentiation in a dose-dependent leading to the enhanced osteogenic proteins expressions of ALP, Runx2, and Collagen I, and subsequently stimulating bone formation [ 181 ]. Additionally, in vitro and in vivo studies showed that OA inhibited TNF-α, MAPK, and PI3-Akt signaling pathways, the results of which were further validated through molecular docking, leading to increased bone salt deposition and accelerated calcification, and hence to an improved bone architecture [ 182 ]. In contrast, having investigated OA bone protective effects in vivo in lipopolysaccharides-induced bone loss in mice, Zhao et al revealed that OA inhibited the receptor activator of nuclear factor kappa-B ligand (RANKL) levels, but without influencing the RANKL-induced up-regulation of the NF-kB/Akt pathways.…”
Section: Oleanolic Acidmentioning
confidence: 99%
“…The endogenous mechanisms underlying changes in metabolites are unclear. In recent years, network pharmacology has had an extensive applicational value in many fields, including the discovery of effective ingredients, drug–target identification, and research on mechanism of action (Y. Wu, Gao, et al, 2021). Rather than looking for a single causative gene or a drug acting on only a single target, network pharmacology considers the entire drug–disease network with the aim of finding multi‐target drugs (Gertsch, 2011).…”
Section: Introductionmentioning
confidence: 99%